2002
DOI: 10.1603/0022-2585-39.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the Mosquitoes <I>Anopheles minimus, An. sinensis,</I> and <I>An. saperoi</I> (Diptera: Culicidae) from the Ryukyu Archipelago, Japan, to the Rodent Malaria <I>Plasmodium yoelii nigeriense</I>

Abstract: The susceptibility of three anopheline mosquitoes, Anopheles minimus Theobald, An. sinensis Wiedemann, and An. saperoi Bohart & Ingram, from the Ryukyu Archipelago to the rodent malaria, Plasmodium yoelii nigeriense was examined to find new vectors other than An. stephensi Liston for rodent malaria studies in the laboratory. The survival rate of the mosquitoes after feeding on mice infected with P. y. nigeriense was also examined. The Beech strain of An. stephensi from India was compared with An. minimus from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The Anopheles sinensis Wiedemann is a major malaria vector in China and other southeastern Asia countries with wide distribution from Afghanistan to northern China, Korea, Japan, Taiwan, and southward into western Indonesia [1-5]. An investigation of mosquito abundance in Yancheng, Jiangsu, China showed that An.…”
Section: Introductionmentioning
confidence: 99%
“…The Anopheles sinensis Wiedemann is a major malaria vector in China and other southeastern Asia countries with wide distribution from Afghanistan to northern China, Korea, Japan, Taiwan, and southward into western Indonesia [1-5]. An investigation of mosquito abundance in Yancheng, Jiangsu, China showed that An.…”
Section: Introductionmentioning
confidence: 99%
“…55 days: P. yoelii in An. saperoi (Toma et al., 2002)], yet at the time the sporozoites invade the glands the mosquitoes reportedly mount a significant immune response (transcription of ICHIT, IGALE20, GNBP and defensin is upregulated) (Dimopoulos et al., 2001). Reconciling these observations requires the conclusion either that the response is sustained for such a brief period that the invading sporozoite survives the ineffectual attack; that the sporozoite is insusceptible to the responses mounted, or as has been shown, key lethal immune factors, e.g.…”
Section: Molecular Interactions Between Parasite and Vectormentioning
confidence: 99%